Neural GDFS: Neural Network Guided DFS for Progressive Cluster Performance on Large Data Set (Global Journal of Computer Science and Technology, 2015)
GlusterFS is the most advanced Distributed File System. GlusterFS uses Devis Meyer2019;s Hashing algorithm as a one way hashing function to save file across the cluster network. Based on GlusterFS, we introduce a new kind of DFS known as NeuralGDFS. NeuralGDFS will incorporate the probabilistic neural network to identify the most probable Brick in which requested file might be located. We also studied GlusterFS performance in virtual cloud environment.